Listening to the Arts: poetical possibilities in research - Fischer, Rosa Maria Bueno (Revista Brasileira de Estudos da Presença, 2021)
This essay discusses methodological possibilities for conducting research using creative artistic processes as references. I ask: how can experimentation be valued, as well as notes of works in progress, and registers of flashes from life, without losing the rigor of theoretical discussions or an attentive look at urgent ethical and political needs of the present? Supported by Foucault, Hadot, Benjamin and others, I discuss topics from the work of Kiarostami, Clarice Lispector, Italo Calvino, and Pina Bausch. With these and other examples, including comments on a study in progress, I propose ways of reasoning poetically by fearlessly appropriating lessons from the arts.